GOOD AND CLEAN GOVERNMENT DALAM SISTEM TATA KELOLA PEMERINTAHAN DI INDONESIA - Junaidi Sholat; Rahmat Suhargon; Arjunawa Arjunawa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Good Governance and Clean Government is a collection of functions contained in a series of processes to achieve the goals of an organization, institution or activity (government bureaucracy, companies, environmental management, etc.) that have been previously determined, through the utilization of existing resources including human resources. Management aims to ensure that all available assets and resources can be utilized in such a way that the expected output and outcome can be obtained. The problem is How is the Management Function of Good and Clean Government, How is Good and Clean Government in the Governance System in Indonesia. The purpose of management can be considered achieved or successful if the output and results obtained are in accordance with the 8 indicators of good governance, namely: based on law (rule of law), accountable, transparent, responsive, inclusive & equitable, consensus, participatory, efficient and effective. Good and clean governance is all aspects related to the control and supervision of the power held by the Government in carrying out its functions through formal and informal institutions. To implement the principles of Good Governance and Clean Government, the Government must implement the principles of accountability and efficient resource management. Improving governance is a long-term effort and requires commitment from the government, society, and non-governmental organizations. Keywords: Governance, Government Abstrak: Good Governance and Clean Government merupakan kumpulan fungsi-fungsi yang terdapat di dalam rangkaian proses untuk mencapai tujuan organisasi, institusi atau kegiatan (birokrasi pemerintahan, perusahaan, pengelolaan lingkungan, dan lain-lain) yang sudah ditetapkan sebelumnya, melalui pemanfaatan sumber daya yang ada termasuk sumber daya manusia. Pengelolaan bertujuan agar seluruh aset dan sumber daya yang tersedia dapat didayagunakan sedemikian rupa sehingga dapat diperoleh luaran (output) maupun hasil (outcome) yang diharapkan. Adapun menjadi permasalah yaitu Bagaimana Fungsi Pengelolaan good and clean government, Bagaimana Good and clean government dalam sistem Tata kelola pemerintahan di Indonesia. Tujuan pengelolaan dapat dianggap tercapai atau berhasil apabila luaran maupun hasil yang diperoleh adalah sesuai dengan 8 indikator tatakelola yang baik (good governance), yaitu: berdasarkan hukum (rule of law), akuntabel, transparan, responsif, inklusif & berkeadilan, konsensus, partispatif, efisien dan efektif. Tata pemerintahan yang baik dan bersih (Good Governance and Clean Government) adalah seluruh aspek yang terkait dengan kontrol  dan pengawasan terhadap kekuasaan yang dimiliki  Pemerintah dalam menjalankan fungsinya melalui institusi formal dan informal. Untuk melaksanakan prinsip Good Governance and Clean Government, maka Pemerintah harus  melaksanakan prinsip-prinsip akuntabilitas dan pengelolaan sumber daya secara efisien. Memperbaiki tata kelola pemerintahan adalah upaya jangka panjang dan memerlukan komitmen dari pemerintah, masyarakat, dan lembaga swadaya masyarakat. Kata kunci: Tata Kelola, Pemerintahan